[Use of oxygen during neonatal resuscitation] [Article in Italian] • Uso dell'ossigeno nella rianimazione del neonato - Roberto Antonucci; Annalisa Porcella; Luca Antonucci (Hygeia Press di Corridori Marinella, 2014)
Immediately after birth, the newly born infant undergoes physiological changes including lung aeration, decrease of pulmonary vascular resistance and initiation of pulmonary gas exchange. Under particular circumstances, this transition process is not adequately accomplished, thus resulting in perinatal asphyxia. In the past decade, remarkable changes have occurred in attitudes towards the use of oxygen in the delivery room. Although oxygen is a lifesaving therapy in neonatal resuscitation, high oxygen concentrations may be harmful to term infants, and especially to preterm infants. In fact, the use of high concentrations of oxygen in the first minutes after birth can lead to an excessive release of free oxygen radicals and to subsequent oxidative stress, with potential damage to multiple organs including the brain, lungs, eyes, and gastrointestinal tract. In 2010, the American Heart Association published revised guidelines for neonatal resuscitation including the recommendations on the measurement and monitoring of oxygenation status and on oxygen supplementation in the delivery room. Some key points of these recommendations are the following: (1) the clinical assessment of skin color is a poor indicator of oxygenation immediately after birth; (2) pulse oximetry provides rapid, continuous and accurate measurement of both oxygenation and heart rate during delivery room resuscitation; (3) the provision of blended oxygen during neonatal resuscitation should be aimed at maintaining oxygen saturations similar to those of uncompromised babies born at term. This paper reviews the available evidence on the management of supplemental oxygen during neonatal resuscitation at birth, and also highlights knowledge gaps.   Articoli Selezionati del "3° Convegno Pediatrico del Medio Campidano" · Guspini · 25 Maggio 2013 Guest Editor: Roberto Antonucci